Groaning and grunting: Investigating sound correspondences in the English lexicon - Mael Farina (Lexis: Journal in English Lexicology)
Phonesthemes can be defined as meaning-carrying sound elements that challenge the arbitrariness of language (first acknowledged by Jespersen [1922] and Firth 1930]). Conventional morphological theories (Bolinger [1950], Blust [1988]) struggle to pin down their origin and behaviour [Kwon & Round 2014]. In English, they appear as meaning-carrying consonant onsets, such as gr- in the words grumble, groan, grunt, grieve or grudge, which all relate to a form of complaint (Waugh [1994: 59]). Psycholinguistic (Bergen [2004]) and statistical (Drellishak [2006]) data have brought evidence for the existence of phonesthemes both in the mental and institutional lexicon. They have also been demonstrated to play a regulation role in the construction of meaning and organisation of the lexicon (Smith [2022b], Benczes [2019], Tsur & Gafni [2022]). As transitory elements between phonology and morphosemantics, phonesthemes call for a need to investigate phonological aspects of lexicology. This paper shows how sounds can carry a semantic dimension from a usage-based approach. I apply a twofold method, combining a lexicographic analysis in the OED, and a corpus analysis in the OEC using the distributional tool Sketch Engine. The lexicographic analysis revealed four semantic traits associated with the phonestheme gr-: 1) bad humour or negative emotions (grump, grunch, grutch, grouse, grisly), 2) unpleasant sensations (grit, grind, grate), 3) unpleasant or deep sounds (groan, growl, grunt, graunch, gruntle), and 4) prehension movements (grasp, grip, grab). The aim of this paper is to test the validity of those results across a usage-based corpus. The words groan, grunt, grudge, grip and grasp were selected as a case study sample. This paper shows that certain phonesthemic words share a semantic space and similar collocational behaviour, while others do not. In particular, clustering of phonesthemic words and expressive markers in context are at stake for groan and grunt, and for grudge to a lesser extent, but not so much in the case of grip and grasp.